(untitled) (Journal of the College of Basic Education, 2022)
The process of introducing reforms and manifestations of civilizational development is considered one of the difficult tasks that accompanied the emergence and development of the Saudi state, and perhaps the first important work done by Ibn Saud was to establish security inside the country, so the pilgrimage caravans heading to and leaving the holy places in the Hijaz began to travel on safe roads with the protection of men Security, after the pilgrims were previously exposed to looting and looting during their travels, after entering the Hijaz, Asir and Hail, as well as Al-Ahsa overlooking the Arabian Gulf, in the Kingdom of Hijaz, Najd and its annexes, and achieving the unity of the land in the Arabian Peninsula, so it was necessary to introduce aspects of life modern to the new state,